Is there a Gender Gap in Preferences for Public Spending? Evidence from Germany - Tina Haußen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In several empirical contributions researchers have found a gender gap in preferences for public spending. This paper analyzes the persistence of these gender gaps when income differences between individuals are taken into consideration. Using survey data from the years 1996 and 2006 of German respondents, we show that gender gaps in preferences vanish when we control for individual income relative to the German median income. The larger this income ratio, the lower the preferences for social security (health care, retirement and unemployment) but the larger the preferences for education spending. Controlling for pseudo individual income (the actual available income if income is shared between all household members), gender gaps in health care and retirement reappear. This may reflect an insurance motive of women who fear to lose the benefits from sharing income within the household.
Keywords: J16; H50; D70; 330